Oxygen precipitation in Ge-doped Czochralski-silicon at 900 °c investigated by in situ high energy x-ray diffraction - Li, Zhen; Will, Johannes; Yang, Deren (AIP Advances, 2020)
In this study, we compare the real-time oxygen (O) precipitation kinetics of heavily germanium (Ge)-doped Czochralski-silicon (Cz-Si) at 900 °C - under different pre-annealing conditions - with those of undoped Cz-Si. We follow in situ the evolution of the Bragg intensity in Laue transmission geometry at elevated temperature and identify both diffusion-driven growth and Ostwald ripening of the O precipitates. We build on our past results, where we observed that although Ge-doping at 800 °C facilitates grown-in precipitates, it has no influence on the nucleation rate. Our present results indicate that within a diffusion-driven growth model, Ge-doping influences the nucleation rate at 650 °C and has no impact at 450 °C. These results shed further light on the origin of various thermal historical effects in Cz-Si samples with high levels of Ge doping.
CRIS-Team Scopus Importer:2020-11-06